Isolation of Alkaline and Neutral Proteases from Aspergillus flavus var. columnaris, a Soy Sauce Koji Mold - Impoolsup, Attawut (1981)
Two different extracellular proteases, protease I (P-I), an alkaline protease, and protease II (P-II) a neutral protease, from Aspergillus flavus var. columnaris were partially purified by using (NH(4))(2)SO(4) precipitation, diethylaminoethyl-Sephadex A-50 chromatography, carboxymethylcellulose CM-52 chromatography, and Sephadex G-100 gel filtration. The degree of purity was followed using polyacrylamide gel electrophoresis. The activity of P-I was completely inhibited by 0.1 mM phenylmethylsulfonyl fluoride, and that of P-II was completely inhibited by 1 mM ethylenediaminetetraacetate. By using these inhibitors with extracts of wheat bran koji, the proportions of total activity that could be assigned to P-I and P-II were 80 and 20%, respectively. This compared favorably with activities estimated by using polyacrylamide gel electrophoresis slices (82 and 18%, respectively). Extracts from factory-run soybean koji gave comparable results. Both enzymes demonstrated maximum activity at 50 to 55°C and only small changes in activity between pH 6 and 11. For P-I, activity was somewhat higher from pH 8.0 to 11.0, whereas for P-II it was somewhat higher from pH 6 to 9. In the presence of 18% NaCl, the activities of both P-I and P-II dropped by approximately 90 and 85%, respectively. P-I was inferred to possess aminopeptidase activity since it could hydrolyze l-leucyl-p-nitroanilide hydrochloride. P-II was devoid of such activity. The ramifications of the results for factory-produced soy sauce koji are discussed.